Do Analysts Matter for Corporate Tax Planning? Evidence from a Natural Experiment1. (1st August 2018) - Chen, Novia X.; Chiu, Peng‐Chia; Shevlin, Terry
ABSTRACT: We exploit an exogenous shock to analyst coverage as a result of brokerage house mergers and closures to examine whether financial analysts influence the tax‐planning activities of the firms they cover. Using a difference‐in‐differences design, we find that, on average, firms affected by broker mergers and/or closures experience a reduction in their GAAP (cash) effective tax rates (ETR) of 2.5 percent (2.6 percent), relative to control firms, translating into average tax expense (cash tax) savings of 34 (35) million. The treatment effect is more pronounced among firms with lower pre‐event analyst coverage. To explore how analysts affect tax planning, we further document that the treatment effect is greater among firms that lose an analyst who provided an implied ETR forecast in the past, suggesting that analysts influence tax planning via their tax‐specific research efforts. In addition, we find that after merger/closure, weakly governed firms increase their use of aggressive tax strategies, and financially distressed firms experience a larger reduction of cash effective tax rates, relative to control firms. Overall, we provide evidence that a shock to analyst coverage sufficiently changes the cost‐benefit trade‐off of tax planning.